Activation of TMEM16A by natural product canthaxanthin promotes gastrointestinal contraction. Issue 10 (19th August 2020) - Ji, Qiushuang; Shi, Sai; Guo, Shuai; Zhan, Yong; Zhang, Hailin; Chen, Yafei; An, Hailong
Abstract: Transmembrane 16A (TMEM16A), also known as anoctamin 1, is the molecular basis of the calcium‐activated chloride channels. TMEM16A is present in interstitial cells of Cajal, which are the pacemaker cells that control smooth muscle contraction. TMEM16A is implicated in gastrointestinal disorders. Activation of TMEM16A is believed to promote the gastrointestinal muscle contraction. Here, we report a highly efficient, nontoxic, and selective activator of TMEM16A, canthaxanthin (CX). The study using molecular docking and site‐directed mutation revealed that CX‐specific binging site in TMEM16A is K769. CX was also found to promote the contraction of smooth muscle cells in gastrointestinal tract through activation of TMEM16A channels, which provides an excellent basis for development of CX as a chemical tool and potential therapeutic for gastrointestinal dysfunction.